Autorzy:Karolina Wej, Wojciech Babiański, Ewa Szmytkiewicz, Jerzy Janowicz
Wydawnictwo:Nowa Era
Rok wydania:2015
Doprowadź dane wyrażenie do najprostszej postaci.4.58 gwiazdek na podstawie 12 opinii

Doprowadź dane wyrażenie do najprostszej postaci.

4Zadanie
5Zadanie
6Zadanie
7Zadanie
8Zadanie
9Zadanie
10Zadanie
11Zadanie
12Zadanie

`a) \ \ (3x^2-6)/3-(4xy+2x^2)/2=(3x^2)/3-6/3-(4xy)/2-(2x^2)/2=x^2-2-2xyx^2=`

`=-2xy-2`

`b) \ \ (-2y)(3x+y)-2x(x-y)=-2y*3x-2y*y-2x*x-2x*(-y)=`

`=-6xy-2y^2-2x^2+2xy=-4xy-2y^2-2x^2` 

`c) \ \ 2x-[1+(1-x)-(x+2)]=2x-(1+1-x-x-2)=`

`=2x-(2-2x-2)=2x-(-2x)=2x+2x=4x` 

`d) \ \ 2x-[x-(x-2)-(4-x)*(-2x)]=2x-(x-x+2-(4*(-2x)-x*(-2x))=`

`=2x-(2-(-8x+2x^2))=2x-(2+8x-2x^2)=2x-2-8x+2x^2=2x^2-6x-2`